ENHANCING COMMUNITY INCOME THROUGH GINGER CANDY PRODUCTION FROM RED GINGER IN DALIG RAYA VILLAGE - Yasmin Chairunisa Muchtar; Muhammad Anggia Muchtar; Jane Melita Keliat3; Wina Nurfitriani; Ahmad Azmi (RADJA PUBLIKA, 2025)
Dalig Raya Village in Simalungun Regency has great potential in red ginger plants. This plant has various health values ​​and benefits. However, the processing of this plant is still lacking, thus hampering its maximum utilization. By optimizing this potential, Dalig Raya Village can become a center for red ginger processing production that contributes to the local economy and improves community welfare, as well as introducing the health benefits of red ginger to the wider community. Therefore, the community service team conducted community service through the International Community Service Scheme in collaboration with UiTM Penang to carry out activities. The methods used to carry out community service include initial discussions with the community, conducting the production process, and training business management. The results of this community service created a red ginger candy product that acts as an anti-cancer, lowers blood sugar and cholesterol, strengthens the immune system, and helps ward off bacterial and viral infections while reducing arthritis symptoms. The PKM team also provided training on how to make ginger candy products. This activity not only provides knowledge but also has the potential to improve public health through the use of herbal plants.